Lymphatic Fate Specification: An ERK-controlled Transcriptional Program - Yu, Pengchun (Microvasc Res, 2014)
Lymphatic vessels are intimately involved in regulation of water and solute homeostasis by returning interstitial fluid back to the venous circulation and play an equally important role in immune responses by providing avenues for immune cell transport. Defects in the lymphatic vasculature result in a number of pathological conditions, including lymphedema and lymphangiectasia. Knowledge of molecular mechanisms underlying lymphatic development and maintenance is therefore critical for understanding, prevention and treatment of lymphatic circulation-related diseases. Research in the past two decades has uncovered several key transcriptional factors (Prox1, Sox18 and Coup-TFII) controlling lymphatic fate specification. Most recently, ERK signaling has emerged as a critical regulator of this transcriptional program. This review summarizes our current understanding of lymphatic fate determination and its transcriptional controls.